Cloud Computing: An Internet Based Computing - Singh, Hardeep (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Present paper focuses on the overview of Cloud Computing. Cloud Computing is an Internet-based computing; where resources, software and information are provided to computers on-demand, like a public utility; is emerging as a platform for sharing resources like infrastructure, software and various applications. This paper does a literature survey on some of the prominent applications of Cloud Computing, and how they meet the requirements of reliability, availability of data, scalability of software and hardware systems and overall customer satisfaction.